DEMONOPOLISASI PT. KAI (PERSERO) DAN PT. PELINDO (PERSERO) PENGUATAN SISTEM EKONOMI DEMOKRASI - Putu Samawati Saleh (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2019)
AbstractDemonopolization of PT KAI (Persero) and PT Pelindo (Persero), intend to make State Owned Enterprise (SOEs) as an independent corporation by balancing between  profit motives and running a business for public benefit. The opening up of opportunities for private companies to become competitors of SOEs which is a company that has been running a monopoly business, aiming to make SOEs as large corporations that are survive and compete, also remain an agent of development. Strengthening SOEs was done through normative by using documentary research. SOEs is expected to be the main business entity that plays a role in national development, by combining corporate/business and public service principles, which are able to be independent and compete globally but still rely on the concept of economic democracy as a distinctive feature of the Indonesian nation. IntisariDemonopolisasi BUMN Persero yang dilakukan terhadap PT KAI (Persero) dan PT Pelindo (Persero), menghendaki BUMN Persero sebagai korporasi yang mandiri yang mampu menyeimbangkan antara tujuan kegiatan usaha untuk profit motif sekaligus menjalankan usaha untuk kemanfaatan umum. Dibukanya peluang perusahaan swasta menjadi kompetitor BUMN Persero yang selama ini menjalani usaha secara monopoli, bertujuan untuk menjadikan BUMN Persero sebagai korporasi besar yang kuat bertahan dan bersaing, serta tetap menjadi agent of development. Penguatan terhadap BUMN Persero dilakukan melalui penelitian normatif dengan mengguakan documentary research. BUMN Persero diharapkan dapat menjadi badan usaha utama yang berperan dalam pembangunan nasional, dengan memadukan prinsip-prinsip korporat/bisnis dan pelayanan publik, yang mampu mandiri dan bersaing secara global tetapi tetap berpijak pada konsep ekonomi demokrasi sebagai ciri khas bangsa Indonesia.